Paris when it sizzles [videorecording (DVD)] - Quine, Richard, 1920-1989; Holden, William, 1918-1981; Hepburn, Audrey, 1929-1993; Aslan, Grégoire, 1908-1982; Coward, Noel, 1899-1973; Duvivier, Julien, 1896-1967; Jeanson, Henri (Paramount, 2001)
A screenwriter with a three-day deadline for a script asks a secretary to help concoct ideas.